2011
DOI: 10.1111/j.1365-2753.2011.01661.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Web‐based clinical decision support system to improve abdominal aortic aneurysm screening in a primary care practice

Abstract: Rationale, aims and objectivesThe United States Preventive Services Task Force recommends a one-time screening for abdominal aortic aneurysm (AAA) with ultrasonography for men aged 65 to 75 years who have ever smoked. However, despite a mortality rate of up to 80% for ruptured AAAs, providers order the screening for a minority of patients. We sought to determine the effect of a Web-based point-of-care clinical decision support system on AAA screening rates in a primary care practice.MethodsWe conducted a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
0
16
0
9
Order By: Relevance
“…This patient population is self-insured; thus, PCIM has developed strategies including case management of chronic illnesses and EMR clinical decision support [26] to assist primary care providers with preventative services. Mayo Clinic has standardized care process models [27] throughout Mayo Clinic for chronic diseases including both HF with preserved and reduced EF.…”
Section: Methodsmentioning
confidence: 99%
“…This patient population is self-insured; thus, PCIM has developed strategies including case management of chronic illnesses and EMR clinical decision support [26] to assist primary care providers with preventative services. Mayo Clinic has standardized care process models [27] throughout Mayo Clinic for chronic diseases including both HF with preserved and reduced EF.…”
Section: Methodsmentioning
confidence: 99%
“…KP SoCal also reported that AAA screening was slowly implemented throughout all of their regional medical centers and clinics [18]. The authors of the Mayo Clinic Rochester study also cautioned that some physicians may reject new technology and software systems that would hinder effective delivery of AAA screening and management strategies for detected AAA [7]. This could negatively influence new patient enrollment for AAA screening among health systems using Medicare.…”
Section: Barriers To Aaa Screening Using An Emrmentioning
confidence: 95%
“…The intent of the SAVE and Dare to CARE programs was to raise cardiovascular health awareness for the older population. In 2008, the Mayo Clinic in Rochester, Minnesota, implemented a Web-based clinical decision support system and EMR to help improve their AAA screening programs among primary care clinics within the Rochester region [7]. Furthermore, there is recently a clinical trial evaluating screening for vascular diseases, including AAA disease, in the urban areas of the state of Illinois [16].…”
Section: Other Aaa Screening Programsmentioning
confidence: 99%
“…9 Similar improvement in screening for abdominal aortic aneurysms was noted using programmed reminders. 10 Clinical reminders positively affected osteoporosis screening rates. 11 Beneficial effects of automated clinical reminders were not limited to preventive screening.…”
mentioning
confidence: 99%